2021
DOI: 10.3892/or.2021.8046
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone suppresses the progression of colonic carcinoma by increasing the activity of the GADD45α/JNK/c‑Jun signalling pathway

Abstract: Colorectal cancer (CRC) is the third most diagnosed cancer worldwide. Progesterone is associated with a decreased risk of CRC and leads to a favourable prognosis. However, the specific mechanism by which progesterone suppresses malignant progression remains to be elucidated. In the present study, the level of progesterone was first analysed in 77 patients with CRC, and immunohistochemistry was performed to detect the expression of progesterone receptor (PGR) in the paired specimens. The correlations between pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…The present data correlate with many earlier studies and emphasise the chemopreventive effects of E2 that could involve inhibition of CRC progression by ERβ-induced cell cycle arrest and apoptosis in malignant enterocytes ( 18 , 20 23 , 57 ). Our study also underscores the previously reported anti-cancer activities of P4 against CRC ( 19 , 24 , 25 , 56 ), which appear to be equal to those of E2 monotherapy, both in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The present data correlate with many earlier studies and emphasise the chemopreventive effects of E2 that could involve inhibition of CRC progression by ERβ-induced cell cycle arrest and apoptosis in malignant enterocytes ( 18 , 20 23 , 57 ). Our study also underscores the previously reported anti-cancer activities of P4 against CRC ( 19 , 24 , 25 , 56 ), which appear to be equal to those of E2 monotherapy, both in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, elevated systemic testosterone levels and higher expression of ERα and AR proteins in CRC were associated with larger tumours, poor differentiation, advanced clinical stages, and worse outcomes in both genders ( 15 , 26 28 ). Hence, our data and results from prior reports ( 14 16 , 19 , 28 , 45 , 46 ) suggest that testosterone with AR and ERα could promote CRC development, while E2 and P4, alongside ERβ and PGR, may act as tumour suppressors.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations